Bleed or clot? managing bleeding in post thrombolysis patient with massive pulmonary embolism who underwent recent major cancer surgery - Balakrishnan, Sivasubramaniam; Mohamad Zahir, Mohd Zulkifli; Draman, Che Rosle; Wan Ali, Wan Ahmad Syahril Rozli; Ibrahim, Ismail (International Islamic University Malaysia, 2022)
A 51-year-old lady with invasive left breast cancer had a syncopal attack following acute chest pain on day 1 post-mastectomy. She was hypotensive and her electrocardiogram showed ST elevation at anterior leads. She had received systemic thrombolysis therapy with an excellent initial symptomatic response and ECG resolution. However, echocardiogram and computed-tomography pulmonary angiogram later showed evidence of massive pulmonary embolism. The treatment was complicated with significant bleeding from the surgical site which required a total of 11 units of packed cells, 4 units of fresh frozen plasma, 4 units of platelet, 6 units of cryoprecipitate and prothrombin complex concentrate; in order to control the bleeding along with local compression. As the haemostasis was achieved, anticoagulation was cautiously initiated, initially with unfractionated heparin followed by low-molecular-weight heparin. Eventually, she received rivaroxaban to complete her course of treatment. She made an excellent recovery on follow-up review and is planned for further treatment for her breast cancer. This case portrayed the complexity of managing a concurrent event of massive thrombosis and significant bleeding, which required a diligent assessment of both risks to ensure the best patient’s outcome.